Association between maternal parenting styles and behavioral problems in children with ASD: Moderating effect of maternal autistic traits - Lin, Xiujin; Su, Xi; Huang, Saijun; Liu, Zhilin; Yu, Hong; Wang, Xin; Lin, Lizi; Cao, Muqing; Li, Xiuhong; Jing, Jin (Frontiers in Psychiatry, 2023)
Background: Children with autism spectrum disorder (ASD) are at high risk of experiencing externalizing and internalizing problems. This study aims to reveal how maternal parenting styles and autistic traits influence behavioral problems in children with ASD. Methods: This study recruited 70 2-5 years children with ASD and 98 typically developing (TD) children. The Parental Behavior Inventory (PBI) and Autism-Spectrum Quotient (AQ) were used to collect the maternal parenting styles and autistic traits, respectively. The children’s behavioral problems were reported by the mothers using the Strengths and Difficulties Questionnaire (SDQ). Hierarchical moderated regression analyses were used to determine whether maternal autistic traits moderated the association between parenting style and behavioral problems in the children. Results: Compared to TD children, children with ASD exhibited more severe externalizing and internalizing problems (t = 4.85, p < 0.01). The ASD group scored lower in the maternal supportive/engaged parenting style than the TD group (t = 3.20, p < 0.01). In the TD group, maternal AQ Attention switching domain was positively correlated with internalizing problems in the children (β = 0.30, p = 0.03). In the ASD group, hostile/coercive parenting style was significantly correlated with externalizing problems in the children (β = 0.30, p = 0.02), whereas maternal AQ Attention switching domain was negatively correlated with externalizing problems (β = –0.35, p = 0.02). Moreover, the maternal AQ Attention switching domain moderated the association between hostile/coercive parenting style and children’s externalizing problems (β = 0.33, p = 0.04). Conclusions: Among ASD children, a hostile/coercive parenting style can increase the risks of children’s externalizing problems especially in the context of high levels of maternal attention switching problems. Hence, the current study has important implications for the clinical practice of early family-level interventions for children with ASD.